From perception to consciousness : searching with Anne Treisman - Wolfe, Jeremy M.; Robertson, Lynn C. (Oxford series in visual cognition., 2012)
Anyone interested in the study of attention will have had some exposure to the work of Anne Treisman. Anne Treisman has been one of the most influential cognitive psychologists in the last 50 years. Her research and theoretical insights have influenced a variety of disciplines, including vision sciences, auditory sciences, cognitive psychology, cognitive neurosciences, philosophy, psychiatry, neuropsychology, and behavioral neurology. She is best known for her work on attention. Early in her career, much of that work involved auditory stimuli. Her later work has been primarily in the realm of visual attention. She has been especially concerned with the interactions among visual perception, attention, and memory as they relate to conscious and unconscious experience. Her Feature Integration Theory has been one of the organizing ideas in the field for three decades. While still a graduate student at Oxford, she helped launch the modern study of attention. In the present volume, several of her most influential papers are reprinted (including some of the harder to find early work). To accompany these reprints, the editors invited experts to comment and/or to show how their own work had been shaped by Treisman's ideas and findings. The result is a scientifically rich ride through the world of ideas inspired by Treisman's work. The contributed chapters include discussions of auditory and visual attention, the role of features in selection, parallel and serial processing, and automaticity. They describe the roots and evolution of Feature Integration Theory and related models like Guided Search. They explore the interactions of attention and perception at the cognitive, neuropsychological, and biological levels. Readers can consider the critical role of binding in perception, the role of attention in scene perception, as well as the influence of cognitive load, memory, reflection, and perceptual learning on early and late processing. They will see how methods to study conscious perceptual awareness have evolved over the years.